High Level of Pretreatment and Acquired Human Immunodeficiency Virus Drug Resistance in El Salvador: A Nationally Representative Survey, 2018–2019. (3rd November 2022) - Girón-Callejas, Amalia; García-Morales, Claudia; Mendizabal-Burastero, Ricardo; Quezada, Alma; Ruiz, Lisette; Arguera, Nelly; Sorto, Salvador; Nieto, Ana I; Tapia-Trejo, Daniela; López-Sánchez, Dulce M; Pérez-García, Marissa; Cruz, Luis; et al.
Abstract: Background: Human immunodeficiency virus drug resistance (HIVDR) can negatively impact the effectiveness of antiretroviral therapy (ART). We aimed to estimate the prevalence of pretreatment HIVDR (PDR) among ART initiators and the prevalence of viral load (VL) suppression and acquired HIVDR among individuals receiving ART for 12 ± 3 months (ADR12) and ≥48 months (ADR48) in El Salvador. Methods: Nationally representative cross-sectional PDR, ADR12 and ADR48 surveys were conducted among adults with HIV from October 2018 to August 2019, following World Health Organization-recommended methods. Demographic and clinic data and blood specimens were collected. Results: Two hundred sixty participants were enrolled in the PDR survey, 230 in ADR12 and 425 in ADR48. Twenty-seven percent (95% confidence interval [CI], 17.1%–39.9%) of ART initiators had PDR to efavirenz or nevirapine. The prevalence of VL suppression was 88.8% (95% CI, 83.1%–92.8%) in ADR12 and 80.5% (95% CI, 76.6%–84.0%) in ADR48 surveys. Among people with HIV receiving a first-line nonnucleoside reverse transcriptase inhibitor (NNRTI)-based ART regimens and with unsuppressed VL, the prevalence of ADR to efavirenz or nevirapine was 72.0% (95% CI, 32.3%–93.3%) and 95.0% (68.5%–99.4%) in the ADR12 and ADR28 surveys, respectively. ADR12 to boosted protease inhibitors (PI/r) or integrase strand transfer inhibitors (INSTIs) was not observed. ADR48 was 1.3% (95% CI, 0.2%–9.6%) and 2.1% (0.3%–13.7%), respectively. Conclusions: Programmatic improvements in ART delivery are urgently needed in El Salvador to address the high levels of resistance to efavirenz or nevirapine among ART initiators and the low VL suppression prevalence among individuals on treatment.